Effects of Conditional Cash Transfers (CCT) in anti-poverty programs: An empirical approach with panel data for the Mexican case of PROSPERA-oportunidades (2002-2012) - Odra Angélica Saucedo Delgado; Vivian Kadelbach; Leovardo Mata Mata (Economies, 2018)
Conditional Cash Transfer Programs (CCT) have been implemented in México and Latin America since the late 1990's. This type of program focuses on providing social government services by way of direct cash transfers to poor families that are often conditioned to the use of public education and health services. Despite the apparent short-term success of these CCT programs in the Latin American context, there still is much debate about whether CCT programs are effective in alleviating poverty. This paper analyzes the effectiveness of conditional cash transfer programs as a long-term incentive in the use of public services-health and education-among beneficiary families of PROSPERA-Oportunidades in Mexico. The Average Effect of Treatment on the Treated (ATT) for the time period 2002-2012 is estimated based on data from the Mexican Family Life Survey (MxFLS) using Propensity Score Matching (PSM). The results show that the program's impact on the use of preventive health and education services by poor families cannot be sustained in the long-term, which puts in doubt the effectiveness of this social protection intervention program in combating poverty in Mexico.
Keywords: 330; poverty; conditionality; social protection; panel data analysis; Sustainable Development Goals (SDGs)